2017
DOI: 10.3917/dev.174.0233
|View full text |Cite
|
Sign up to set email alerts
|

Traduction française de l’autoquestionnaire MIBS (Mother to Infant Bonding Scale) et validation comme évaluation du lien mère-nouveau-né en maternité

Abstract: A partir de 48 heures du post-partum, 78 mères ont répondu à l’autoquestionnaire MIBS ( Mother-to-Infant Bonding Scale ) traduit en français ainsi qu’à 3 autres questionnaires. Vingt-quatre heures plus tard, un entretien pédopsychiatrique permettait d’évaluer la relation mère-enfant. Les puéricultrices remplissaient le MIBS, en imaginant les réponses des mères. Le MIBS permettait un dépistage satisfaisant des difficultés du lien mère-enfant (sensibilité = 0,9 et spécificité = 0,8 pour un seuil supérieur ou éga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The MIBS has shown good initial psychometrics ( 1 ). The validated French version was used in this study ( 32 ). This measure has also been previously used with fathers to asses bonding, showing adequate internal reliability across both mothers and fathers ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…The MIBS has shown good initial psychometrics ( 1 ). The validated French version was used in this study ( 32 ). This measure has also been previously used with fathers to asses bonding, showing adequate internal reliability across both mothers and fathers ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…In his study, Bienfait, found the existence of 13% of difficulties of motherchild relationship [5]. His study made it possible to determine the diagnosis threshold of mother-child link disruption from a MIBQ score equal to or greater than 2, but strongly advising the passage of an interview as a means of ruling out false positives.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, the baby has often been considered as a passive being, influenced by his environment and, in the first place, by his mother [1]. Early assessment of mother-infant relationship is priority goal in maternity, because of its importance for the child's psycho-emotional and somatic development and for the prevention of abuse [2] [3] [4] [5]. As well as reducing of maternal and newborn hospital stay in industrialized countries in recent decades [6], this task is becoming more complex and encourages the development of practical tools to help teams perform this assessment early [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores are summed to create a total score, with a higher score indicating worse mother-to-infant bonding. The MIBS has shown good initial psychometrics,122 and has been validated in French 123…”
Section: Methodsmentioning
confidence: 99%